Od poezji „oszczędnej w słowa” do „trudnej” prozy dla dzieci. Przekłady literatury słoweńskiej w latach 2016—2017 - Gawlak, Monika (Przekłady Literatur Słowiańskich, 2019)
The aim of the article is to review the Slovenian literature translated into Polish in 2016 and 2017. The author of the article presents translations of Slovenian poetry, prose, books addressed to children, and drama. Some of the important publishers are indicated along with the most active translators, their probable motivations, and ways of obtaining funds for their publications. The author of the article is also interested in reception of traslated Slovenian literature in the target literary field.